2021
DOI: 10.1155/2021/9946628
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation Study on Compression Characteristics of Gravelly Soil Mixture Based on Soft Servo Method

Abstract: Because of complex mechanical properties and deformation mechanism, gravel soil mixture is an important medium of concern in the field of geotechnical engineering. Based on the continuous-discontinuous coupling algorithm formed by the structure shell elements and the particle discrete element method (PFC3D), the soft servo loading of the sample is realized, and the typical triaxial compression test data are used to calibrate mesoscale parameters. Furthermore, the numerical tests under different rock contents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…However, the discrete element method can reflect these characteristics well (Cundall and Strack, 1980). This finding confirms that particle flow code (PFC) can effectively reflect the physicomechanical properties and deformation failure mechanism of gravel media (Ju et al, 2018;Gong and Liu, 2015;Meng et al, 2018;Ning et al, 2021).…”
Section: Cemented Conglomerate Accumulation 1407supporting
confidence: 62%
“…However, the discrete element method can reflect these characteristics well (Cundall and Strack, 1980). This finding confirms that particle flow code (PFC) can effectively reflect the physicomechanical properties and deformation failure mechanism of gravel media (Ju et al, 2018;Gong and Liu, 2015;Meng et al, 2018;Ning et al, 2021).…”
Section: Cemented Conglomerate Accumulation 1407supporting
confidence: 62%
“…Ham et al (2010) [20] employed the two-phase mixture theory suggested by Gutierrez (2005) [21] in an effort to study the influence of gravel content on initial dry density and compression index of D-G-S. In this theory, the overall void ratio e(P) of the mixed material is a function of the gravel content (P) by mass and is related to the void ratio of sand (e s ) and void ratio of gravel (e g ), as shown in Equation (1).…”
Section: 𝑒(𝑃) = 𝑒 (1 − 𝑃) + 𝑒 𝑃mentioning
confidence: 99%
“…Gravel-soil mixture is an important medium of concern in the field of geotechnical engineering [1], and several studies in the literature have been conducted to clarify the engineering characteristics of gravel materials including investigations on the effect of gravel content on precompression stress [2][3][4][5][6][7][8][9][10][11][12][13]. However, the mechanical properties and deformation mechanism of gravelly soils are complex because of inhomogeneity, high porosity, and under-compaction [14].…”
Section: Introductionmentioning
confidence: 99%